The Significance Of Accounting Records Based On SAK ETAP At The Makassar City Coffee Shop For Micro, Small, And Medium Enterprises - Nur Asmi Ainun Kamal; Fika Hartina Sari; Sitti Jamiah HA; Melsa Jumliana; Rahadian Cahyadi (CV. AFDIFAL MAJU BERKAH, 2024)
This research aims to determine the suitability of accounting records at Warkop MSMEs in Makassar City based on SAK ETAP. and to find out the obstacles faced by Coffee Shop For Micro, Small, And Medium Enterprises in Makassar City when they do not implement accounting records in accordance with SAK ETAP. The method used in this research uses a qualitative approach. The subjects in this research are Coffee Shop For Micro, Small, And Medium Enterprises in Makassar City including Coffee Shop Boeken Huis, Coffee Shop Resota, and Coffee Shop Malaku. This research uses qualitative data types and primary data sources and secondary data. Data collection techniques use observation, interviews and documentation. The data analysis used in this research is descriptive data analysis using analysis steps: Classifying, Identifying, Analyzing, processing data and making conclusions. The results of this research show that: Accounting records carried out by Coffee Shop Managers are still carried out very simply. only record cash incoming and cash outgoing from business activities without recording journals or ledgers. The recording carried out by Coffee Shop depends on the understanding of each Coffee Shop manager. This is due to the lack of knowledge of Coffee Shop owners regarding SAK ETAP, there are no special experts in the field of Accounting and warkop managers have never attended accounting training from the government or those in charge of Micro, Small, And Medium Enterprises